Danish general practitioners’ self-reported competences in end-of-life care - Winthereik, Anna (Scand J Prim Health Care, 2016)
OBJECTIVE: General practitioners (GPs) are pivotal in end-of-life (EOL) care. This study aimed to assess GP-reported provision of EOL care and to assess associations with GP characteristics. DESIGN: Population-based questionnaire study. SETTING: Central Denmark Region with approximately 1.3 million inhabitants. SUBJECTS: All 843 active GPs in the Central Denmark Region were sent a questionnaire by mail. MAIN OUTCOME MEASURES: Responses to 18 items concerning four aspects: provision of EOL care to patients with different diagnosis, confidence with being a key worker, organisation of EOL care and EOL skills (medical and psychosocial). RESULTS: In total, 573 (68%) GPs responded. Of these, 85% often/always offered EOL care to cancer patients, which was twice as often as to patients with non-malignancies (34–40%). Moreover, 76% felt confident about being a key worker, 60% had a proactive approach, and 58% talked to their patients about dying. Only 9% kept a register of patients with EOL needs, and 19% had specific EOL procedures. GP confidence with own EOL skills varied; from 55% feeling confident using terminal medications to 90% feeling confident treating nausea/vomiting. Increasing GP age was associated with increased confidence about being a key worker and provision of EOL care to patients with non-malignancies. In rural areas, GPs were more confident about administering medicine subcutaneously than in urban areas. CONCLUSION: KEY POINTS: GPs are pivotal in end-of-life (EOL) care, but their involvement has been questioned. Hence, GPs’ perceived competencies were explored. GPs were twice as likely to provide EOL care for patients with cancer than for patients with non-malignancies. EOL care was lacking clear organisation in general practice in terms of registering palliative patients and having specific EOL procedures. GPs were generally least confident with their skills in terminal medical treatment, for example, using medicine administered subcutaneously.